Analysis Of The Factors Affecting Employee Job Satisfaction On Employee Performance - Murtiasih, Sri; Hartanto, Septian Tri; Iqbal, Muhammad (CV. Syntax Corporation Indonesia, 2025)
The purpose of this study is to analyze factors that affect job satisfaction, namely leadership, skills and work environment on job satisfaction and its implications on employee performance. The data in this study uses primary data, which was obtained through the distribution of questionnaires through google forms. The sampling of this study uses saturated sampling techniques (census), so that the sample used in this study is all employees of PT KAI Karawang Branch which totals 94 people. The test stages carried out are: descriptive statistics, measurement model (outer model), structural model (inner model) and path analysis (path analysis). The testing tool used is SmartPLS. The results of this study show that the variables of leadership, skills and work environment have a significant effect on job satisfaction. Job Satisfaction variables have a significant effect on employee performance. Leadership variables, skills and work environment also have a direct effect on employee performance, but the influence is smaller than the indirect influence, namely through job satisfaction, so job satisfaction is a factor that mediates the influence of leadership, skills and work environment on employee performance.